2018
DOI: 10.3390/buildings8120183
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Enables Innovative Timber Structure Adoption in Construction

Abstract: Timber structures in construction have become more popular in recent years. Nevertheless, besides the complexity of designing, contracting and building these structures, a barrier to their market growth is the complexity of their supply chain relationships encompassing architects, engineers, builders and suppliers. The objective of this study is therefore to identify and characterize the supply chain relationships shared by these stakeholders within a massive timber construction project. Twenty-seven semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Most of the time, respondents preferred talking about collaboration relationships shared with other stakeholders. Gosselin et al [86] identified collaboration relationships between stakeholders in structural timber building supply chains. In this study, collaboration relationships refer to informal exchanges of various sorts.…”
Section: Key Partnershipsmentioning
confidence: 99%
“…Most of the time, respondents preferred talking about collaboration relationships shared with other stakeholders. Gosselin et al [86] identified collaboration relationships between stakeholders in structural timber building supply chains. In this study, collaboration relationships refer to informal exchanges of various sorts.…”
Section: Key Partnershipsmentioning
confidence: 99%
“…Similarly to the innovative cases studied by Pulkka et al (2016), WMC projects involve innovativeness and working with novel aspects in a collaborative manner (see e.g. Gosselin et al 2018), creating an interesting setting for the business ecosystem concept to be applied, as presented below. (Clough, 2015;Klee, 2015).…”
Section: A Business Ecosystem Approach To Wmc Projectsmentioning
confidence: 99%
“…Relational contracts are necessary because multilayer chain subcontracting systems lead to the poor coordination of information flows due to the long communication chains among stakeholders (Tam et al, 2011;Loosemore, 2014). Gosselin et al (2018) find that too much owner contract controlcommon in traditional contracting practices but not relational contractsleads to a perceived lack of trust and hinders contractor cooperation (Hartmann and Caerteling, 2010). To overcome the problem, some researchers encouraged that conflicts or disputes could be settled by renegotiations and mediations rather than penalties or litigations (Akintoye and Main, 2007).…”
Section: Contractual Enablers 421 Relational Contractsmentioning
confidence: 99%